PENGARUH BERAT MOLEKUL ADITIF PADA PENAMPANG MELINTANG DAN KARAKTERISTIK MEMBRAN SERAT BERONGGA POLISULFON, YANG DIAMATI DENGAN ALAT SCANNING ELECTRON MICROSCOPY - Syahril Ahmad (Research Center for Chemistry - LIPI, 2000)
Cross section of polysulfone membranes hollow fiber spun bydry - wet process have been studied. Composition of membraneobserved composed of 16% Polysulfone (PS) , 64% dimethylAcetamide (DMAc) as solvent and 18% Polyetylene glycol (PEG)as additive. Molecular weight of polyetylene glycols used were 200,300 and 400 Daltons. Fiber of membranes were charaterized bydextrane solution to find rejection coefficient and molecular weightcut - off of the membrane. Cross sections of hollow fiber membraneswere observed by Scanning Electron Microscopy (SEM).Results of the experiment show that, molecular weight ofpolyethylene Glycol additif used in spinning of hollow fibermembrane affects form of cross section of substructure andmolecular weight cut - off the membrane obtained. This researchwas aimed to predict the pore size of membrane made based onmolecular weight of additive used.